Phylogeography of Poorly Dispersing Net-Winged Beetles: A Role of Drifting India in the Origin of Afrotropical and Oriental Fauna - Sklenarova, Katerina; Chesters, Douglas; Bocak, Ladislav (PloS one, 2013)
Ancient dispersal history may be obscured by subsequent dispersal events. Therefore, we intend to investigate the biogeography of metriorrhynchine net-winged beetles, a group characterized by limited dispersal propensity. We used DNA data to construct phylogenies and the BayesTraits and RASP programs to identify putative ancestral areas. Further, we inferred ultrametric trees to estimate the ages of selected nodes. The time frame is inferred from tectonic calibrations and the general mutation rate of the mitochondrial genes. Metriorrhynchini consists of two lineages with Afro/Oriental and Australian distributions. The basal lineages originated in Eastern Gondwana after the split of Australia, India and Madagascar; the Afrotropical and Madagascar Metriorrhynchini separated from the Oriental clades 65 and 62 mya. Several already diversified lineages colonized continental Asia 55-35 mya. A few genera of the Australian clade dispersed to the Oriental region 5-15 mya and reached Eastern India and Southern China. Only Xylobanus crossed the Makassar Strait to Sulawesi and does not occur further to the east. The current distribution of Metriorrhynchini is a result of drifting on continental fragments and over-sea dispersal events limited to a few hundreds of kilometers. We conclude that: (1) Afrotropical and Madagascar lineages originated independently from dispersal events during India's drift to the north and the Mozambique Channel completely isolates the respective faunas since then; (2) Oriental fauna is a recently established mixture of the Indian and Australian lineages, with predominance of the older Indian clades; (3) The fauna of islands located north of Australia colonized Sulawesi after collision with the Sundaland margin and the species rich Australian lineages did not reach Western Wallacea or the Philippines. Our results suggest an impact of subtle differences in biological characteristics on biogeographic history of individual lineages, when mostly lowland and flower-visiting lineages were able to disperse across sea channels.
Keywords: Animals; Madagascar; Mutation Rate; Asia; Animal Migration; Phylogeography; Coleoptera; DNA, Mitochondrial; India; brouci; Genes, Mitochondrial; mutační rychlost; fylogeografie; mitochondriální geny; mitochondriální DNA; Asie; migrace zvířat; zvířata; Indie; Madagaskar